CD38: an ecto-enzyme with functional diversity in T cells - Ghosh, Alip; Khanam, Arshi; Ray, Krishanu; Mathur, Poonam; Subramanian, Ananya; Poonia, Bhawna; Kottilil, Shyam (Frontiers in Immunology, 2023)
CD38, a nicotinamide adenine dinucleotide (NAD)+ glycohydrolase, is considered an activation marker of T lymphocytes in humans that is highly expressed during certain chronic viral infections. T cells constitute a heterogeneous population; however, the expression and function of CD38 has been poorly defined in distinct T cell compartments. We investigated the expression and function of CD38 in naïve and effector T cell subsets in the peripheral blood mononuclear cells (PBMCs) from healthy donors and people with HIV (PWH) using flow cytometry. Further, we examined the impact of CD38 expression on intracellular NAD+ levels, mitochondrial function, and intracellular cytokine production in response to virus-specific peptide stimulation (HIV Group specific antigen; Gag). Naïve T cells from healthy donors showed remarkably higher levels of CD38 expression than those of effector cells with concomitant reduced intracellular NAD+ levels, decreased mitochondrial membrane potential and lower metabolic activity. Blockade of CD38 by a small molecule inhibitor, 78c, increased metabolic function, mitochondrial mass and mitochondrial membrane potential in the naïve T lymphocytes. PWH exhibited similar frequencies of CD38+ cells in the T cell subsets. However, CD38 expression increased on Gag-specific IFN-γ and TNF-α producing cell compartments among effector T cells. 78c treatment resulted in reduced cytokine production, indicating its distinct expression and functional profile in different T cell subsets. In summary, in naïve cells high CD38 expression reflects lower metabolic activity, while in effector cells it preferentially contributes to immunopathogenesis by increasing inflammatory cytokine production. Thus, CD38 may be considered as a therapeutic target in chronic viral infections to reduce ongoing immune activation.